2020
DOI: 10.7554/elife.62765
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomics of white-eyes, a ‘great speciator’, reveals Indonesian archipelago as the center of lineage diversity

Abstract: Archipelagoes serve as important ‘natural laboratories’ which facilitate the study of island radiations and contribute to the understanding of evolutionary processes. The white-eye genus Zosterops is a classical example of a ‘great speciator’, comprising c. 100 species from across the Old World, most of them insular. We achieved an extensive geographic DNA sampling of Zosterops by using historical specimens and recently collected samples. Using over 700 genome-wide loci in conjunction with coalescent species t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 98 publications
2
23
0
Order By: Relevance
“…White-eyes, genus Zosterops, represent one of the most remarkable avian cases of rapid radiation in the Pleistocene. Although most of the diversity is found in the Indo-Pacific archipelago, one lineage colonized Africa and diversified throughout the sub-Saharan continent (Cai et al, 2019;Gwee et al, 2020). Recent molecular work suggest that the many populations, which are characterized by broad, white eyerings and replace each other in different Afromontane areas, do not represent a monophyletic clade but are interspersed in the phylogeny among generally more widespread lowland forms (Martins et al, 2020).…”
Section: Superfamily Sylvioidea "Warblers" In the Broader Sensementioning
confidence: 99%
“…White-eyes, genus Zosterops, represent one of the most remarkable avian cases of rapid radiation in the Pleistocene. Although most of the diversity is found in the Indo-Pacific archipelago, one lineage colonized Africa and diversified throughout the sub-Saharan continent (Cai et al, 2019;Gwee et al, 2020). Recent molecular work suggest that the many populations, which are characterized by broad, white eyerings and replace each other in different Afromontane areas, do not represent a monophyletic clade but are interspersed in the phylogeny among generally more widespread lowland forms (Martins et al, 2020).…”
Section: Superfamily Sylvioidea "Warblers" In the Broader Sensementioning
confidence: 99%
“…Conversely, some of the most interesting examples of speciation are also from species with high dispersal rates. For example, the white-eyes complex of birds, one of the classic examples of ‘great speciators’ comprises of approximately 100 species in the old world, most of them being restricted to islands 26 , 52 . Great speciators paradoxically can disperse across great distances, often colonizing entire archipelagos but diversifying at the same time 17 , 26 , 52 .…”
Section: Gene Flow and Islands As Drivers Of Biodiversitymentioning
confidence: 99%
“…For example, the white-eyes complex of birds, one of the classic examples of ‘great speciators’ comprises of approximately 100 species in the old world, most of them being restricted to islands 26 , 52 . Great speciators paradoxically can disperse across great distances, often colonizing entire archipelagos but diversifying at the same time 17 , 26 , 52 . Recent work on the phylogenomic relationships between various taxa revealed Borneo to be the major centre for diversity and an evolutionary hotspot for the white-eyes 26 .…”
Section: Gene Flow and Islands As Drivers Of Biodiversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular phylogenetic studies (Moyle et al 2009; Irestedt et al 2013; Jønsson et al 2014; Andersen et al 2013, 2014, 2015; Pedersen et al 2018; Kearns et al 2020) have confirmed that great speciators represent rapid and geographically complex lineage radiations. However, those same attributes, combined with limited genetic sampling, have impeded precise evolutionary reconstruction of these radiations (though see Gwee et al [2020] and Manthey et al [2020]).…”
Section: Introductionmentioning
confidence: 99%